Pengembangan Rencana Pelaksanaan Pembelajaran (RPP) Menggunakan Model Problem Based Learning (PBL) Pada Pembelajaran Tematik Di Kelas IV SDN Kota Bengkulu - Vika Rethusa; Herman Lusa; Hasnawati Hasnawati (JURIDIKDAS, 2020)
This research is motivated by the problem of the many teachers in elementary schools who have not implemented Thematic learning in the 2013 Curriculum properly. This study aims to produce a Learning Implementation Plan (RPP) using the Problem Based Learning (PBL) Learning Model in grade IV elementary school which can be used as a teacher's reference in carrying out learning in class. This research is a Thiagarajan and Sammel research. However, this research was only carried out until the third stage, namely Develop. Validation is carried out by curriculum experts. The developed lesson plans were rated as practical by 2 teachers from Bengkulu City Elementary School. Data analysis techniques used descriptive statistical analysis of the results of expert validation assessment and teacher responses and qualitative descriptive analysis of the comments of the validator and the teacher. This research produces a Thematic Implementation Plan (RPP) using the Problem Based Learning (PBL) Learning Model with expert research of 89% with a very valid category and practicality assessment of 88.67% with an excellent category as the final product of development.       Keywords: RPP, Development, PBL, Thematic